Reform of the Law on Political Party Dispute Resolution in Indonesia to Realize Legal Certainty - Ismail Marjuki (Greenation International Journal of Law and Social Sciences, 2025)
Political party disputes in Indonesia frequently raise serious issues that have implications for political stability and the sustainability of democracy. To date, the mechanism for resolving political party disputes still faces various problems, ranging from dualism of authority, inconsistent decisions, to weak implementation of laws and regulations. These conditions result in legal uncertainty that can reduce public trust in the legal system and democracy. Therefore, legal reform in resolving political party disputes is needed to provide a more effective, consistent, and certainty-oriented mechanism. This study uses a normative juridical approach by examining the provisions of the 1945 Constitution of the Republic of Indonesia, Law Number 2 of 2011 concerning Political Parties, Law Number 7 of 2017 concerning General Elections, and relevant Constitutional Court Decisions. Conceptual analysis is also used to assess the need for legal reform to strengthen legal certainty and democratization. The results of the study indicate that legal reforms for resolving political party disputes can be directed at three main things: (1) strengthening the role of an independent judiciary free from political intervention, (2) harmonization of regulations between political party laws, election laws, and judicial regulations, and (3) the application of the principles of justice, certainty, and benefit in a balanced manner. With legal reforms, it is hoped that the resolution of political party disputes can be more effective, just, and realize legal certainty which is the main foundation for the consolidation of democracy in Indonesia.